Expanded Somatic Mutation Spectrum of MED12 Gene in Uterine Leiomyomas of Saudi Arabian Women - Ajabnoor, Ghada M. A.; Mohammed, Nesma Amin; Banaganapalli, Babajan; Abdullah, Layla Saleh; Bondagji, Ola Nabeel; Mansouri, Nisma; Sahly, Nora Naif; Vaidyanathan, Venkatesh; Bondagji, Nabeel; Elango, Ramu; Shaik, Noor Ahmad (Frontiers in Genetics, 2018)
MED12, a subunit of mediator complex genes is known to harbor genetic mutations, mostly in exon 2, causal to the genesis of uterine leiomyomas among Caucasian, African American and Asian women. However, the precise relationship between genetic mutations versus protein or disease phenotype is not well explained. Therefore, we sought to replicate the MED12 mutation frequency in leiomyomas of Saudi Arabian women, who represents ethnically and culturally distinct population. We performed molecular screening of MED12 gene (in 308 chromosomes belonging to 154 uterine biopsies), analyzed the genotype-disease phenotype correlations and determined the biophysical characteristics of mutated protein through diverse computational approaches. We discovered that >44% (34/77) leiomyomas of Arab women carry a spectrum of MED12 mutations (30 missense, 1 splice site and 3 indels). In addition to known codon 44, we observed novel somatic mutations in codons 36, 38 and 55. Majority of MED12 mutated tumors 27/30; 90%) showed only one type of genetic change, asserting their deleterious effect on protein function. An interesting inverse correlation between tumor size and LH is observed when tumor is positive to MED12 mutation (p<0.05). Our computational investigations suggest that amino acid substitution mutations in exon-2 region of MED12 might contribute to potential alterations in phenotype as well as the stability of MED12 protein. Our study, being the first one from Arab world, confirms the previous findings that somatic MED12 mutations are critical to development and progression of uterine leiomyomas irrespective of the ethnic background. We recommend that mutation screening, particularly codon 44 of MED12 can assist in molecular diagnostics of uterine leiomyomas in majority of the patients.